The resort : a novel - Ochs, Sara (Sourcebooks Landmark, 2024)
"Five years ago, Cass barely survived a brutal attack that left her family dead. Now a scuba diving instructor in Thailand, she has spent years trying to build a new, anonymous life for herself as one of the Permanents, a group of expats who have claimed the beautiful Thailand destination as their own. The permanents are charming, they're close-knit, and they don't linger on who they were before the island--they're the perfect group for Cass to finally shed her old self. But her dark past is about to catch up with her when Lucy, one of Cass' dive students, turns up dead and she starts getting messages from someone who has discovered who she really is. And that person will stop at nothing until Cass' truth is out and justice has been served"--